2013
DOI: 10.6002/ect.2012.0194
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Hinder Organ Donation: Religio-Cultural or Lack of Information and Trust

Abstract: Objectives: This paper examines factors that influence Malaysian persons with a tertiary level of education on their willingness to donate organs. Materials and Methods: A survey was done in the Klang Valley (Kuala Lumpur and its suburbs) at several designated locations. A total of 1420 people were approached, and we focused the sample of 688 respondents with a tertiary level of education. Respondents were given 2 sets of answers: (1) a religio-cultural category and (2) a structural category. They were allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 5 publications
1
37
0
Order By: Relevance
“…To achieve the study's objectives, on the light of previous studies on organ donation, 5,1216 experts in social science and medicine (Makmor Tumin, Li Yoong Tang, and Mei Chan Chong) collaborated to produce a self-administrated questionnaire. The questionnaire was prepared and distributed in English.…”
Section: Methodsmentioning
confidence: 99%
“…To achieve the study's objectives, on the light of previous studies on organ donation, 5,1216 experts in social science and medicine (Makmor Tumin, Li Yoong Tang, and Mei Chan Chong) collaborated to produce a self-administrated questionnaire. The questionnaire was prepared and distributed in English.…”
Section: Methodsmentioning
confidence: 99%
“…The official Islamic verdict in Malaysia also allows cross-religion and cross-ethnic organ donation and transplantation (24).Organs can be procured from a cadaver or a brain dead donor; however, in most countries, most organs for transplantation are sourced from brain dead donors owing to viability constraints (29). Earlier studies found that the lack of information on organ donation and transplantation caused the Malaysian public to be unwilling to donate (6,34). Although knowledge on organ donation should not be low among people with higher levels of education, surprisingly, this study shows that the three professional groups investigated in this work -HCPs, RLs, and ACAs -lack adequate knowledge on the basic issues of organ donation and transplantation, with RLs showing the worst level of understanding.…”
Section: Discussionmentioning
confidence: 58%
“…Most such studies emphasise the importance of knowledge on organ donation and transplantation in determining willingness to donate organs (4)(5)(6)(7)(8)(9)(10). On the other hand, many authors have also identified the role of religion in guiding people's viewpoints and attitude toward organ donation (7,, people become more willing to donate when they know that religious leaders (RLs) support organ donation (15).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies in Malaysia suggest the possibility of religiocultural factor as the main impediment to organ donation in Malaysia (6, 7), while others suggest low organ donation -especially among the post-secondary education groupas the result of the public lack of trust toward the medical system (8). In another study, there was a proposal that non-fungible incentives would positively influence the way people react to organ donation (9 In the survey, 1420 people were approached, out of which 1311 agreed to do the survey, giving a response rate of around 91.5%.…”
Section: Introductionmentioning
confidence: 99%